Improving the luminescence property of the novel yellow-emitting phosphor SrLa2Sc2O7:Bi3+ with charge compensators (Li+, Na+, K+) and its application in NUV-based white LEDs. Issue 43 (21st October 2022) - Yang, Huifang; Li, Panlai; Ye, Zejun; Huo, Xiaoxue; Wang, Yu; Wu, Qian; Wang, Zhijun
Abstract : In this work, a novel yellow-emitting phosphor SrLa2 Sc2 O7 :Bi 3+ was synthesized by high temperature solid-state method, ranging from 400 nm to 800 nm under near-ultraviolet (NUV) excitation and the full width at half maximum (FWHM) of up to 180 nm. Abstract : In this work, a novel yellow-emitting phosphor SrLa2 Sc2 O7 (SLSO):Bi 3+ was synthesized by a high temperature solid-state method, with a wide coverage from 400 nm to 800 nm under near-ultraviolet (NUV) excitation and the full width at half maximum (FWHM) of up to 180 nm. The phosphor emits bright yellow light, which is observed using optical microscopy. Alkali metal (Li +, Na +, K + ) ions were used as charge compensators to enhance the luminescence intensities of SrLa2 Sc2 O7 :Bi 3+ . Finally, the yellow SrLa2 Sc2 O7 :Bi 3+, Li + and blue Sr5 (PO4 )3 Cl:Eu 2+ phosphors were homogeneously mixed with silica gel and coated on a NUV light emitting diode (LED) at 370 nm to obtain white LEDs with a high color rendering index ( R a = 91.3), a low correlated color temperature (CCT = 4879 K) and color coordinates (0.34, 0.30). This work can provide a good candidate for making white LEDs.